Children's perceptions of fluid milk with varying levels of milkfat - H.M. Keefer; L.R. Sipple; B.G. Carter; D.M. Barbano; M.A. Drake (Journal of Dairy Science, 2022)
ABSTRACT: Schools participating in federal meal programs are limited to serving skim or low-fat (≤1%) flavored and unflavored milk. Few studies have directly addressed child perceptions and preferences for milk containing different amounts of milkfat. The objective of this study was to determine whether children can differentiate between flavored and unflavored fluid milk containing varying levels of milkfat and whether preferences for certain levels of milkfat exist. Flavored and unflavored milks containing 4 different percentages of milkfat (≤0.5, 1, 2, and 3.25%) were high-temperature, short-time processed, filled into half-gallon light-shielded milk jugs, and stored at 4°C in the dark. Milks were evaluated by children (ages 8–13 yr) following 7 d at 4°C. Acceptance testing and tetrad difference testing were conducted on flavored and unflavored milks with and without visual cues to determine if differences were driven by visual or flavor or mouthfeel cues. Child acceptance testing (n = 138 unflavored; n = 123 flavored) was conducted to evaluate liking and perception of selected attributes. Tetrad testing (n = 127 unflavored; n = 129 flavored) was conducted to determine if children could differentiate between different fat levels even in the absence of a difference in acceptance. The experiment was replicated twice. When visual cues were present, children had higher overall liking for 1% and 2% milks than skim for unflavored milk and higher liking for chocolate milks containing at least 1% milk fat than for skim. Differences in liking were driven by appearance, viscosity, and flavor. In the absence of visual cues, no differences were observed in liking or flavor or mouthfeel attributes for unflavored milk but higher liking for at least 1% milk fat in chocolate milk compared with skim was consistent with the presence of visual cues. From tetrad testing, children could visually tell a difference between all unflavored pairs except 2% versus whole milk and could not detect consistent differences between milkfat pairs in the absence of visual cues. For chocolate milk, children could tell a difference between all milk fat pairs with visual cues and could tell a difference between skim versus 2% and skim versus whole milk without visual cues. These results demonstrate that in the absence of package-related flavors, school-age children like unflavored skim milk as well as milk with higher fat content in the absence of visual cues. In contrast, appearance as well as flavor and mouthfeel attributes play a role in children's liking as well as their ability to discriminate between chocolate milks containing different amounts of fat, with chocolate milk containing at least 1% fat preferred. The sensory quality of school lunch milk is vital to child preference, and processing efforts are needed to maximize school milk sensory quality.